Publisher Correction: Neonatal selection by Toll-like receptor 5 influences long-term gut microbiota composition. (15th November 2018) - Fulde, Marcus; Sommer, Felix; Chassaing, Benoit; Vorst, Kira; Dupont, Aline; Hensel, Michael; Basic, Marijana; Klopfleisch, Robert; Rosenstiel, Philip; Bleich, André; Bäckhed, Fredrik; Gewirtz, Andrew; et al.
In Fig. 1d of this Letter, the third group along should have been labelled 'WT' rather than 'Tlr5 '. This has been corrected online.